Periodisasi Pendidikan Islam di Indonesia: Transformasi dari Masa Klasik hingga Modern - Fajar Angga Saputra; Diza Ayatillah Arsyal; Gita Tri Hafsari; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the periodization of Islamic education in Indonesia by analyzing its transformation from the classical era to the modern period through a historical-qualitative approach. The research is based on non-empirical data derived from academic literature, scholarly articles, and relevant historical documents, selected through purposive criteria to ensure academic credibility and thematic relevance. The analysis employs a historical methodology involving heuristic data collection, source criticism, and contextual interpretation, followed by historiographical synthesis to construct a coherent narrative of educational development. The findings reveal that Islamic education in Indonesia has undergone a multidimensional transformation encompassing institutional restructuring, shifts in educational orientation, and the reconstruction of epistemological frameworks. Institutional changes reflect the adaptation of educational systems to socio-political demands, while epistemological developments indicate a transition from dichotomous knowledge structures toward integrative paradigms. Furthermore, contemporary dynamics demonstrate the influence of globalization, digitalization, and intellectual reform in shaping more adaptive and transformative educational models. The study concludes that Islamic education in Indonesia represents a dynamic system that continuously negotiates between tradition and modernity, enabling it to remain relevant within changing global contexts.